(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Background: Frequently, hypertension (high blood pressure) or its disorder occurs during pregnancy, and it remains one of the major causes of maternal and fetal mortality and morbidity associated with pregnancy, as well as the risk of pregnant women with hypertension during pregnancy to cardiovascular disease later in life. However, contrary to the general hypertension guidelines, the reasons for this report include the benefit of normalizing treatment of high blood pressure in pregnant women and potential risks related to decreased prenatal chorionic perfusion, and exposure of the uterus to antihypertensive drugs. This approach is based on a review of previous reports and literature and includes a taxonomic review of the types of blood pressure during pregnancy, the physiological changes in pregnancy that affect blood pressure disorders, the immediate and long-term consequences of hypertension, and the pathophysiology of pre-eclampsia that are related to the disturbance of proteinuria in the body, and the goals of hypertension treatment may reduce meternal severe effects without increased risk of pregnancy loss or neonatal care at a high level. The critical need to investigate the social and economic variables that contribute to the inequities in maternal health care is discussed in our final discussion on the field’s research future. so it is necessary to know the pressure and treat it immediately. Failure to treat high blood pressure can lead to maternal morbidity and mortality, especially during childbirth, or the loss of the fetus significantly. Therefore, in this mini review, we will try to discuss high blood pressure in pregnant women and determine the goals of treatment and preeclampsia caused by high blood pressure. The aim of the review is a quick scientific summary of this disorder that has become common at the present time.Conclusions : Medical consultation should be done in order to improve the health of the mother, as well as the use of optimal medication and pre-pregnancy management in women with or threatened with high blood pressure, and we consider it necessary to inform them of the increased risks to her health and the health of the fetus. Strategies must be in place to predict those most at risk and to determine optimal drug therapies to minimize adverse pregnancy outcomes